2014
DOI: 10.3892/ijo.2014.2302
|View full text |Cite
|
Sign up to set email alerts
|

The selective cytotoxicity elicited by phytochemical extract from Senecio graveolens (Asteraceae) on breast cancer cells is enhanced by hypoxia

Abstract: Breast cancer is the second cause of cancer‑related deaths in woman and the incidence of the disease has increased worldwide, in part due to improvements in early detection. Several drugs with anticancer effects have been extracted from plants in the last 20 years, many of which are particularly effective against breast cancer cells. In particular, we have become interested in the ethanolic extract from Senecio graveolens (synonym of S. nutans), a plant commonly called Chachacoma, in an effort to isolate compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…These results corroborate those shown by Echiburú-Chau et al [6], who by means of the neutral red uptake test observed that at a concentration of 200 μg/mL ethanolic extract of S. graveolens exhibited cytotoxicity in breast cancer cell lines ZR-75-1, MCF-7, and MDA-MB-231 at 24 h of treatment under hypoxic conditions, without damaging the MCF-10F cell line. However, at this concentration, the ethanolic extract of S. graveolens showed a greater cytotoxic effect on the cell line MDA-MB-231 (50 %) com-pared to the other cancer lines ZR-75-1 (9 %) and MCF-7 (6 %) [6]. Finally, both MTT and LDH assays showed that dichloromethane/ methanol and aqueous extracts have cytotoxic effects higher than 100 μg/mL in the PBMCs.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…These results corroborate those shown by Echiburú-Chau et al [6], who by means of the neutral red uptake test observed that at a concentration of 200 μg/mL ethanolic extract of S. graveolens exhibited cytotoxicity in breast cancer cell lines ZR-75-1, MCF-7, and MDA-MB-231 at 24 h of treatment under hypoxic conditions, without damaging the MCF-10F cell line. However, at this concentration, the ethanolic extract of S. graveolens showed a greater cytotoxic effect on the cell line MDA-MB-231 (50 %) com-pared to the other cancer lines ZR-75-1 (9 %) and MCF-7 (6 %) [6]. Finally, both MTT and LDH assays showed that dichloromethane/ methanol and aqueous extracts have cytotoxic effects higher than 100 μg/mL in the PBMCs.…”
Section: Resultssupporting
confidence: 91%
“…It should be noted that in the work of Echiburú-Chau et al [6] they mentioned that the majority compound [4-hydroxy-3-(3-methyl-2-butenyl) acetophenone] of the alcoholic extract presented less cytotoxic activity on different tumour cellular lines than the complete extract. However, in our case, the major compounds (phanurane, damsine, and scoparone) of the dichloromethane/ methanol extract showed greater cytotoxic activity over different tumour cellular lines than the complete extract (▶Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have demonstrated that certain phytochemicals have better selectivity than chemically derived drugs. For example, the ethanolic extract of Senecio graveolens causes selective cytotoxicity in breast cancer cells via hypoxia-mediated mitochondrial dysfunction and oxidative stress (Echiburu-Chau et al, 2014). Ashwagandha leaf extract and its purified component Withanone have been shown to cause selective killing of cancer cells by inducing reactive oxygen species (ROS)-mediated damage (Widodo, Priyandoko, Shah, Wadhwa, & Kaul, 2010).…”
Section: Cancer Chemotherapymentioning
confidence: 99%
“…[4], Senecio graveolens Wedd. [5], and Salicornia brachiata Roxb. [6] practiced worldwide by various traditional healers, and natural products such as Hypnea musciformis [7] and jadomycins [8] biosynthesized by the soil bacteria Streptomyces venezuelae are yet to be screened for its potential therapeutic effects.…”
Section: Introductionmentioning
confidence: 99%